Kajian kes usahawan tani industri cecil sederhana (IKS) bumiputera di Negeri Terengganu - Nuruluda Che Abdullah; Ramlee Mustapha (penerbit ukm, 2009)
Agriculture in this country is experiencing significant transformation towards a more dynamic and competitive sector. This sector is critical in the sense that it is not only contributed to economic growth but also can contribute to creating job opportunities. The development of agro-based small and medium industries (SMI) is emphasised in the nation’s Agriculture Policy because it is expected to enhance the value-added of the agro-products. Even though the move by the government to make Malaysia as a global hub for food producing and chain by 2010, the achievement of SMI Bumiputera agropreneurs is still at low level. This case study utilised quantitative and qualitative approaches. Based on the research objectives and literature review, a set of questionnaires, interview protocol and site visit checklist was developed in order to collect pertinent data for this study. A sample of 10 agropreneurs (5 males and 5 females) in the state of Terengganu was selected based on the set criteria. The study found that, in general, the respondents strongly agreed that their business practices were in order. However, the result of the interview reveals that the participants acknowledged that their marketing strategies were weak. Further, the results of the site visit and document analysis show that, in general, the participants’ management of finances and account was poor.